Entanglement Between Two Mechanical Oscillators in a Dual-Coupling Optomechanical System - Li, Yujie; Deng, Li; Yin, Taishuang; Chen, Aixi (Frontiers in Physics, 2022)
In this paper, we investigate the properties of entanglement of an optomechanical system including two mechanical oscillators, where two mechanical oscillators are coupled with the cavity field in different coupling modes: the interaction between one mechanical oscillator and cavity field is first-order coupling, and the interaction between the other and the cavity field is quadratic coupling. On the one hand, the entanglement between two mechanical oscillators is studied. The influences of the frequency of cavity field, the mass of mechanical oscillators and the temperature of mechanical oscillators on the entanglement between two mechanical oscillators are investigated. On the other hand, for given parameters of the system, we also obtain the entanglement between the cavity field and the mechanical oscillator that has a quadratic coupling. Compared with the entanglement between microscopic particles, the stable macroscopic quantum entanglement between two mechanical oscillators has the characteristics of long existence life and can be reused, and it also plays an important role in quantum information processing and quantum network construction.